Factors Associated with Work Fatigue Symptoms on Bus Service Officers of PT TransJakarta Corridor VI Ragunan - Lukman, Mutiara Sakinah; Mustakim, Mustakim (Disease Prevention and Public Health Journal, 2020)
Background: Work fatigue is a source of problems for workers’ health and safety. According to the Ministry of Manpower, data on occupational accidents in 2017 indicate that the number of occupational injuries was 80,392 cases. This study aims to find out factors related to fatigue symptoms on Bus Service Officers of PT TransJakarta, including age, sex, nutritional status, marital status, medical history, workload, work stress, work shift, and ergonomic status. Method: This study uses an analytical descriptive research design with a cross-sectional design, involving 158 Bus Service Officers at Corridor VI Ragunan PT TransJakarta in July 2018. The data collection was conducted by using questionnaires and with univariate and bivariate data analysis. Results: The results show that there was a significant relationship between work fatigue and work stress (p = 0.000), workload (p = 0.000), ergonomic status (p = 0,000). Besides that, there was no relationship between work fatigue and age, years of service, marital status, medical history, and nutritional status. Conclusion: While those who had no significant relationship were sex, nutritional status, marital status, medical history, and years of service, it is suggested that the company should reevaluate the workload, work stress, work shift with perceived fatigue, providing further training on good body position.